PREVALENSI 10 PENYAKIT TERBANYAK PADA PEKERJA PERKEBUNAN SAWIT DI RUMAH SAKIT TANDUN PT. NUSA LIMA MEDIKA PROVINSI RIAU - DANDI NOVTIARDI; ANCE ROSLINA (JURNAL ILMIAH SIMANTEK, 2023)
Riau Province is an archipelago with an area of 87,023.7 km2 and is the province with the second largest area on the island of Sumatra after South Sumatra Province. It has an area of 2.7 million hectares of oil palm plantations, which is part of Indonesia's oil palm plantation area of 14.3 million hectares. PT. Perkebunan Nusantara V has fields of work, including field workers, factory workers, office employees, and others. Tandun Hospital PT Nusa Lima Medika is a facility prepared by PT Perkebuan V as an employee facility to create occupational safety and health. To determine the prevalence of 10 diseases in oil palm plantation workers at Tandun Hospital PT Nusa V Medik.This study used descriptive quantitative with cross sectional design method of data collection using total sampling technique. The population in this study were all medical records of oil palm plantation workers at Tandun Hospital PT. Nusa Lima Medika based on the criteria to be studied. This study showed that the results seen from the age range of 41-50 years were the highest results, namely 592 patients, the second was in the 31-40 age range, which was 253 patients, and the last was the 20-30 age range, which was as many as 80 patients by showing the prevalence of different diseases in each age, gender and field of work owned by each patient. The highest prevalence of 10 diseases among oil palm workers at Tandun Hospital PT. Nusa Lima Medika Riau Province.